Regulation of the Bone-Specific Osteocalcin Gene by p300 Requires Runx2/Cbfa1 and the Vitamin D3 Receptor but Not p300 Intrinsic Histone Acetyltransferase Activity - Sierra, Jose (American Society for Microbiology, 2003)
p300 is a multifunctional transcriptional coactivator that serves as an adapter for several transcription factors including nuclear steroid hormone receptors. p300 possesses an intrinsic histone acetyltransferase (HAT) activity that may be critical for promoting steroid-dependent transcriptional activation. In osteoblastic cells, transcription of the bone-specific osteocalcin (OC) gene is principally regulated by the Runx2/Cbfa1 transcription factor and is stimulated in response to vitamin D(3) via the vitamin D(3) receptor complex. Therefore, we addressed p300 control of basal and vitamin D(3)-enhanced activity of the OC promoter. We find that transient overexpression of p300 results in a significant dose-dependent increase of both basal and vitamin D(3)-stimulated OC gene activity. This stimulatory effect requires intact Runx2/Cbfa1 binding sites and the vitamin D-responsive element. In addition, by coimmunoprecipitation, we show that the endogenous Runx2/Cbfa1 and p300 proteins are components of the same complexes within osteoblastic cells under physiological concentrations. We also demonstrate by chromatin immunoprecipitation assays that p300, Runx2/Cbfa1, and 1α,25-dihydroxyvitamin D(3) receptor interact with the OC promoter in intact osteoblastic cells expressing this gene. The effect of p300 on the OC promoter is independent of its intrinsic HAT activity, as a HAT-deficient p300 mutant protein up-regulates expression and cooperates with P/CAF to the same extent as the wild-type p300. On the basis of these results, we propose that p300 interacts with key transcriptional regulators of the OC gene and bridges distal and proximal OC promoter sequences to facilitate responsiveness to vitamin D(3).